2019
DOI: 10.2196/13482
|View full text |Cite
|
Sign up to set email alerts
|

Social Jetlag and Chronotypes in the Chinese Population: Analysis of Data Recorded by Wearable Devices

Abstract: Background Chronotype is the propensity for a person to sleep at a particular time during 24 hours. It is largely regulated by the circadian clock but constrained by work obligations to a specific sleep schedule. The discrepancy between biological and social time can be described as social jetlag (SJL), which is highly prevalent in modern society and associated with health problems. SJL and chronotypes have been widely studied in Western countries but have never been described in China. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
4
46
0
Order By: Relevance
“…In accordance with previous studies in adults 31 and pre-school children 32 findings of the present study show that evening-types experienced social jet lag more frequently than morning-types (7% and 3%, respectively). Social jet lag is a term describing misalignment between social and biological time 33 .…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies in adults 31 and pre-school children 32 findings of the present study show that evening-types experienced social jet lag more frequently than morning-types (7% and 3%, respectively). Social jet lag is a term describing misalignment between social and biological time 33 .…”
Section: Discussionsupporting
confidence: 93%
“…However, social jet lag does not exclusively affect adolescents, as it has also been reported in shift workers, whose work during the night leads to a desynchronization of the circadian rhythm [ 191 ], and in young adults [ 192 ]. In contrast, not all populations showed a great social jet lag manifestation; for example, the Chinese population reported the social jet lag less frequently than the European population, and it was not correlated with higher BMI as it typically is in western societies [ 193 ]. Social jet lag represents a possible risk factor or cause for several pathological conditions, such as tumors, type 2 diabetes, and depression [ 194 , 195 , 196 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the combination of both a shift towards later chronotype during adolescence (15) and early school start times (16) , adolescents experience short sleep during the school week and more social jetlag compared with adults (13) . In addition to short sleep duration (17)(18)(19) , some studies indicate that social jetlag is associated with higher BMI (7)(8)(9)(10)(11) and larger waist circumference (7,10) among adults, though other studies indicate a null association (20)(21)(22)(23) . One study that examined the relationship between social jetlag and BMI among adolescents found a positive association (12) , with another demonstrating an association between social jetlag and increased odds of obesity only among females (24) .…”
mentioning
confidence: 99%